A study of centralization of library and information services at the Philippine Sugar Commission - David, Prescy S. (1980)
The Philippine sugar industry, in spite of its many problems and recent reverses in the world market, is still one of the pillars of the country's economy. The nation has continued to maintain its position as the fourth largest exporter of sugar in the world.